NLP META MODEL TO ENHANCE SOFT COMMUNICATION SKILLS IN MOBILE LEGENDS - Mhd Agri Amri; Muhammad Abiyyu De Rossi; Rita Hartati (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
This study explores the application of the Neuro-Linguistic Programming (NLP) Meta Model to enhance soft communication skills in the context of online gaming, specifically Mobile Legends: Bang Bang. Miscommunication, toxic language, and ineffective collaboration are common issues among players in this competitive multiplayer game. By applying the NLP Meta Model—focusing on linguistic patterns of deletion, distortion, and generalization—this research aims to analyze and improve player interactions. Using a qualitative method involving interviews, observations, and conversation analysis, the study demonstrates how targeted questioning techniques can clarify ambiguous language, promote empathetic responses, and foster constructive dialogue. Findings suggest that the NLP Meta Model can significantly contribute to more effective and respectful communication in digital gaming environments, enhancing teamwork and reducing conflict..